Mantera dan amalan kecantikan wanita Bajau: Kajian kes Bajau Kota Belud / Rahmah Abdul Ghani - Rahmah , Abdul Ghani (2018)
Mantra inherited by the Bajau community is relevant till today, especially for beauty, healing, protection, and others. Therefore, the objective of this research is to analyze Mantra and beauty rituals of Bajau women in Kota Belud, Sabah. The data gathered is from selected informants living in several parts within the research area. The research material is composed of various types of Mantra and rituals associated with the beauty of Bajau women which are suited to the research objectives. This study is a qualitative research which uses the data accumulated through observation, interviews and data analysis. The study findings showed that Bajau women still practices Mantra and traditional tips to enhance their beauty and appearance, to be accepted by their community. Bajau women are of the opinion that beauty will allow her to attain love from her family and other community members. This is because outer beauty paired with inner beauty will make family members and the community which constitutes the extended family, easily accepted them.